2022
DOI: 10.3390/ijerph192316039
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Concentrations and Thermal Comfort Analysis at Onsite and Online Educational Environments

Abstract: In building areas with high occupancy, such as classrooms, transmission routes of SARS-CoV-2 are increased when indoor air quality is deficient. Under this scenario, universities have adopted ventilation measures to mitigate contagious environments. However, the lack of adequate equipment or designs in old educational buildings is a barrier to reach minimum requirements. This study aims to quantify the indoor air quality and thermal comfort at universities and compare it to conditions in students’ households. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Regarding indoor air quality, different recommendations about CO 2 maximal concentration and the minimum ventilation rate have been published. Indeed, in order to assess proper ventilation, CO 2 sensors can be installed [27][28][29][30][31]. As they record the level of CO 2 in parts per million (ppm), they are good proxies of indoor air quality, in addition to being easy to use and inexpensive [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding indoor air quality, different recommendations about CO 2 maximal concentration and the minimum ventilation rate have been published. Indeed, in order to assess proper ventilation, CO 2 sensors can be installed [27][28][29][30][31]. As they record the level of CO 2 in parts per million (ppm), they are good proxies of indoor air quality, in addition to being easy to use and inexpensive [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in order to assess proper ventilation, CO 2 sensors can be installed [27][28][29][30][31]. As they record the level of CO 2 in parts per million (ppm), they are good proxies of indoor air quality, in addition to being easy to use and inexpensive [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Here, CO 2 is used as an indicator for the quality of the air exchange, by observing the natural exhalation of the persons present in the room. Monitoring the indoor CO 2 concentration in the context of SARS-CoV-2 has been carried out in various settings, e.g., theatres [19], buses [20], hospitals [21], and classrooms [22][23][24][25]. That this approach is helpful has been shown by, e.g., Di Gilio et al, who derived an effective air exchange strategy for classrooms by using the real-time visualization and monitoring of CO 2 concentrations [25].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that, with this ventilation option, the IAQ is strongly influenced by the outdoor climate (REHVA, 2020) and the behaviour of the occupants (Franceschini & Neves, 2022), being their actions driven by their perception and pursuit of thermal comfort. In fact, various investigations have proven that natural ventilation often fails to provide save indoor environments, resulting in CO2 concentrations over 900 ppm, which exceeds the regulated thresholds (Alegría-Sala, Clèries Tardío, et al, 2022;Gaihre et al, 2014;Gil-Baez et al, 2021). Furthermore, the recommendation to keep doors and windows open to reduce the risk of coronavirus transmission when heating systems were activated led to an increase in energy consumption (Gaspar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A study performed by Leiv M. Mortensen (1994) conclude that lettuce, carrot, and parsley yields exposed to high levels of CO2, up to 900 ppm, resulted in an increase of the production of 18%, 19%, and 17%, respectively. Even if the optimal CO2 concentration should be determined by specific production requirements (Dong et al, 2018), an adequate level of CO2 enrichment can be set between 800 and 1000 ppm (Wang et al, 2022), which is what easily can be found in closed educational environments (Alegría-Sala, Marin-López, et al, 2022). Several methods are employed for the enrichment period, such as during the day and night, just during the day, or simply in the morning or at night.…”
Section: Introductionmentioning
confidence: 99%